Method for preparing electrode for electrolyzing heavy alcohol waste liquid based on nano ultrasonic spraying technology

The preparation of electrolytic heavy alcohol waste liquid electrodes through nano-ultrasonic spraying technology solves the problems of complex process, time-consuming and insufficient stability in the existing technology, and achieves efficient and simple electrode preparation, significantly improves catalytic activity and stability, and is suitable for large-scale applications.

CN119877008APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311389580.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, when preparing high-performance electrolytic heavy alcohol waste liquid electrodes, the process is complex, time-consuming, and insufficient stability and catalytic activity, making it difficult to meet the needs of large-scale applications.

Method used

The electrolytic heavy alcohol waste liquid electrode was prepared by nano-ultrasonic spraying technology. The catalyst powder was synthesized, the catalyst slurry and polymer additive solution were arranged, and the porous catalytic layer was formed by vacuum emulsification shear, high-speed stirring and ultrasonic dispersion technology, which simplified the process and improved efficiency.

Benefits of technology

It realizes the preparation of high stability and high catalytic activity electrodes at room temperature, which significantly improves the electrooxidation rate of ethylene glycol, and has better electrode stability, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877008A_ABST
    Figure CN119877008A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-performance electrolytic heavy alcohol waste liquid electrode based on a nano ultrasonic spraying technology. The method specifically comprises the following steps: synthesizing catalyst powder through a chemical coprecipitation method; preparing catalyst slurry, a high polymer additive solution and a pore forming agent solution; dispersing the catalyst slurry through vacuum emulsification shearing, high-speed stirring and ultrasound; and respectively carrying out nano ultrasonic spraying on the two surfaces of the composite foamed nickel electrode of the heavy alcohol waste liquid electrolysis device by using the slurry and the solution. By adopting the method disclosed by the invention, the porous catalyst layer which is higher in electrocatalytic activity and more stable can be prepared. The electrode prepared by the process can stably operate for a long time, and degradation of ethylene glycol in the waste liquid and coupled hydrogen production are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of inorganic functional electrode materials, and in particular to a method for preparing a high-performance electrode for electrolyzing heavy alcohol waste liquid based on nano-ultrasonic spraying technology. Background Art

[0002] Hydrogen energy is a secondary energy source with a wide range of sources, clean and carbon-free, flexible and efficient, and rich application scenarios. It is an ideal medium to promote the clean and efficient use of traditional fossil energy and support the large-scale development of renewable energy. Water electrolysis using intermittent electricity represents a promising commercial technology for industrial hydrogen production. As the reverse reaction of hydrogen combustion, water electrolysis uses water as the only raw material and is a closed hydrogen cycle with no carbon emissions. It is considered to be the most green and sustainable method at this stage and can play an important role in the revolution of energy production and consumption. However, in water electrolysis, water consumption will squeeze out precious water resources. At present, the available wastewater far exceeds the demand for hydrogen production by water electrolysis. Using innovative technologies to achieve hydrogen production from sewage is an effective way to protect and effectively utilize water resources.

[0003] The market demand for chemical ethylene glycol wastewater treatment is huge, and the capital market behind it is also relatively large. If a technological breakthrough can be achieved in coupling the electrolysis of ethylene glycol wastewater with hydrogen production, it will bring huge economic value and social effects, and become a typical demonstration under the "3060 dual carbon target".

[0004] Due to the oxygen evolution reaction [OER, E 0 =1.23V (vs.RHE)] is a very slow four-electron transfer process. The reaction process has a high energy barrier and kinetic limitations. The development of catalysts has become the key to hydrogen production technology by electrolysis of water. The theoretical oxidation potential of ethylene glycol in the electrolysis of ethylene glycol wastewater is low [EGOR, E 0 =-0.81V (vs.RHE)], which will replace the OER process to achieve efficient water electrolysis. At present, the electro-oxidation of ethylene glycol mostly uses precious metals Pb, Pt and Au, but these precious metal-based catalyst materials are scarce and expensive, and CO is generated during the electrolysis process and adsorbed on the electrode surface, causing electrode poisoning and inactivation, and poor stability. Therefore, in order to achieve large-scale application, transition metal oxides, hydroxides, phosphides and sulfides have been widely studied to form electrocatalysts that take into account both cost-effectiveness and high activity and stability.

[0005] Patent application 201910104915.X discloses a method for preparing core-shell CoP-Ni2P nanorods, which uses a two-step hydrothermal method to regulate the Ni2 The thickness and surface morphology of the P shell can be adjusted to achieve HER and OER reactions, but the process of this method is relatively complicated and only involves the regulation of the specific surface area of ​​the obtained nanorods, and does not involve the regulation of their stability; Patent application 202211586937.2 discloses a method for preparing a carbon-coated manganese-doped CoP bifunctional water decomposition electrode, which adopts a hydrothermal and phosphating synthesis method. The prepared electrode has good hydrogen evolution performance, oxygen evolution performance and stability, but the process is also complicated and cumbersome, taking about 24 hours; Patent application 202310096720.1 discloses a porous carbon carrier nano non-precious metal hydrogen evolution electrode and a preparation method, which uses a highly porous silk fabric carbonization interface to drive the electrodeposition of nano nickel plating. This is achieved thanks to the fine control of electrocatalytic deposition on carbonized silk fibers, but the amount of catalyst deposition during the electrodeposition process is difficult to calculate and control, and a high temperature of about 1000°C is required during the preparation. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a non-precious metal electrode which has a simple process, short time consumption, and can obtain good stability and good ethylene glycol oxidation performance at room temperature.

[0007] The present invention provides a method for preparing an electrode for electrolyzing heavy alcohol waste liquid based on nano-ultrasonic spraying technology, which is characterized by comprising the following steps:

[0008] Step S1: synthesizing catalyst powder;

[0009] Step S2: preparing catalyst slurry;

[0010] Step S3: preparing a polymer additive solution;

[0011] Step S4: preparing a porogen solution;

[0012] Step S5: dispersing the catalyst slurry by vacuum emulsification shearing, high-speed stirring and ultrasound;

[0013] Step S6: performing nano-ultrasonic spraying on the electrode for electrolysis of heavy alcohol waste liquid; wherein the electrode is a foamed nickel electrode;

[0014] Step S7: Turn over the electrode for electrolysis of heavy alcohol waste liquid, and repeat step S6 to spray the other side thereof to obtain the electrode for electrolysis of heavy alcohol waste liquid containing a porous catalytic layer.

[0015] Preferably, in step S1, the catalyst is copper-doped nickel hydroxide (Cu-Ni(OH)2), and its synthesis process comprises the following steps:

[0016] S101: dissolving nickel salt and copper salt in deionized water to obtain a catalyst salt solution, and controlling the concentrations of nickel salt and copper salt in the obtained solution to be 0.098 mol / L and 0.002-0.01 mol / L, respectively; wherein the nickel salt is Ni(NO3)2·6H2O, and the copper salt is Cu(NO3)2;

[0017] S102: adding sodium hydroxide to the catalyst salt solution to generate flocculent precipitate, adjusting the pH to 13.5 and then standing for 30 minutes;

[0018] S103: After the solution has been allowed to stand, the supernatant is discarded, and deionized water is added and centrifuged in a centrifuge for 5 minutes. The operation is repeated twice to obtain catalyst powder.

[0019] Preferably, in step S2, a first solvent is added to the catalyst, and the mass ratio of the catalyst to the first solvent is controlled to be 1:(20-40); wherein the first solvent is one or more of water, ethylene glycol, isopropanol and propylene glycol.

[0020] Preferably, in step S3, the polymer is polyamic acid salt, and a second polar solvent is added to the polyamic acid salt, and the mass ratio of the polyamic acid salt to the second polar solvent is 1:(10-40); wherein the second polar solvent is one or more of ethylene glycol, isopropanol and propylene glycol.

[0021] Preferably, in step S4, the pore-forming agent is ammonium bicarbonate, and a third solvent is added to the pore-forming agent, and the mass ratio of the pore-forming agent to the third solvent is 1:(10-40); wherein the third polar solvent is one or more of ethylene glycol, isopropanol and propylene glycol.

[0022] Preferably, step S5 includes the following sub-steps:

[0023] S501: vacuum emulsification shearing and high-speed stirring: the catalyst slurry obtained in step S2 is subjected to vacuum emulsification shearing, and high-speed stirring is performed simultaneously with vacuum emulsification shearing;

[0024] S502: Ultrasonic dispersion: Ultrasonic dispersion is performed on the catalyst slurry after vacuum emulsification shearing and high-speed stirring in step S501 to obtain dispersed catalyst slurry.

[0025] Preferably, in step S501, the rotation speed of the vacuum emulsification shearing is 10000-20000 r / min, the time is 10-60 min, and the temperature is 20-35°C.

[0026] Preferably, in step S502, the ultrasonic dispersion time is 20-60 min, the ultrasonic power is set to 600-1200 W, and the ultrasonic frequency is set to 20-40 KHz.

[0027] Preferably, in step S6, the nickel foam electrode requires the following pretreatment steps:

[0028] S601: Immerse the commercial nickel foam in acetone solution and ultrasonically wash it for 15-20 minutes to remove organic matter on the surface;

[0029] S602: immersing the nickel foam obtained in step S601 in a hydrochloric acid aqueous solution for ultrasonic washing for 15-20 minutes; wherein the volume ratio of hydrochloric acid to water in the hydrochloric acid aqueous solution is 1:3;

[0030] S603: ultrasonically washing the nickel foam obtained in step S602 with deionized water until the aqueous solution becomes neutral;

[0031] S604: The nickel foam obtained in step S603 is rinsed with anhydrous ethanol and then placed in a vacuum oven for drying at 60° C. for 30 min.

[0032] Preferably, in step S6, the pretreated nickel foam is placed on a spraying base, the prepared catalyst slurry, polymer additive solution and pore-forming agent solution are delivered to the spraying chamber through different flow channels, and the spraying equipment parameters are set so that the catalyst loading on the electrode is 2 mg / cm 2 The flow rate of polymer additive solution is 0.8 ml min -1 The flow rate of the pore-forming agent solution is 0.3 ml min -1 , until the spraying is completed; then the electrolysis heavy alcohol waste liquid electrode containing a porous catalytic layer obtained by ultrasonic spraying is placed in a vacuum oven for drying at 60°C for 30 minutes to obtain the electrolysis heavy alcohol waste liquid electrode product.

[0033] Compared with the prior art, the electrode for electrochemical oxidation of ethylene glycol wastewater provided by the present invention first synthesizes a catalyst powder of a specific ratio by a chemical coprecipitation method, and then prepares a certain amount of catalyst slurry, a polymer additive and a pore-forming agent solution. The electrode with high stability and high catalytic activity can be prepared by ultrasonic spraying equipment. The preparation method provided by the present invention is simple, efficient and has good adjustability. The thickness and size of the catalyst layer on the electrode can also be easily customized. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is an X-ray diffraction pattern of the catalyst electrode prepared in the embodiment of the present invention.

[0035] Figure 2 The field emission scanning electron microscope images of the catalyst electrodes obtained in the examples of the present invention and the comparative examples are shown in FIG. 1 , wherein (a) is the SEM image of the catalyst electrode obtained in Example 1 of the present invention, and (b) is the SEM image of the catalyst electrode obtained in Comparative Example 2.

[0036] Figure 3 The linear sweep voltammetry curves of the catalyst electrode prepared in the embodiment of the present invention for oxidizing ethylene glycol wastewater, (a) is the LSV curve of the catalyst electrode obtained in embodiment 1 of the present invention, and (b) is the LSV curve of the catalyst electrode obtained in embodiment 2 of the present invention.

[0037] Figure 4 The linear sweep voltammetry curves of the catalyst electrode prepared in the comparative example of the present invention for oxidizing ethylene glycol wastewater, (a) is the LSV curve of the catalyst electrode obtained in comparative example 1 of the present invention, and (b) is the LSV curve of the catalyst electrode obtained in comparative example 2 of the present invention. DETAILED DESCRIPTION

[0038] The present invention will be further described in detail below in conjunction with specific embodiments to provide a better understanding of the content of the present invention, but the present invention is not limited to the following embodiments.

[0039] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0040] Embodiment 1:

[0041] 1) Catalyst synthesis

[0042] Take 28.5g Ni(NO3)2·6H2O and 0.375g Cu(NO3)2 and dissolve them in 1L deionized water. Stir magnetically for 10 minutes. The concentrations of nickel salt and copper salt in the aqueous solution are 0.098mol / L and 0.002mol / L, respectively. Add sodium hydroxide to the solution until the pH reaches 13.5. After standing for 30 minutes, pour out the supernatant, then add deionized water and centrifuge. Repeat the centrifugation twice to obtain catalyst powder.

[0043] 2) Prepare catalyst slurry, polymer additive solution and pore-forming agent solution

[0044] Prepare catalyst slurry: take 3g of catalyst, then add 50ml of deionized water and 20ml of ethylene glycol to obtain catalyst slurry, so that the solid content of the catalyst is 4wt%, and then disperse the catalyst slurry by vacuum emulsification shearing, high-speed stirring and ultrasound. Set the speed of vacuum emulsification shearing to 10000r / min, the time to 30min, the temperature to 25°C, the ultrasonic dispersion time to 30min, and the ultrasonic power to 800W.

[0045] Prepare polymer additive solution: take 1.2 g of polyamic acid and dilute it to 5 wt % with ethylene glycol.

[0046] Prepare the porogen solution: take 0.5 g of ammonium carbonate and dilute it to 5 wt % with isopropanol.

[0047] 3) Nickel foam pretreatment

[0048] Firstly, the commercial nickel foam was immersed in an acetone solution and ultrasonically washed for 15 minutes to remove surface organic matter; secondly, the nickel foam washed with acetone was immersed in a hydrochloric acid aqueous solution and ultrasonically washed for 15 minutes, and the volume ratio of hydrochloric acid to water was 1:3; then, the nickel foam washed with hydrochloric acid was ultrasonically washed with deionized water until the aqueous solution was neutral; finally, the nickel foam rinsed with deionized water was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C for 30 minutes.

[0049] 4) Place the pretreated nickel foam on the spraying base, deliver the prepared catalyst slurry, polymer additive solution and pore-forming agent solution to the spraying chamber through different flow channels, and set the spraying equipment parameters so that the catalyst loading is 2 mg / cm 2 The flow rate of polymer additive solution is 0.8 ml min -1 The flow rate of the pore-forming agent solution is 0.3 ml min -1 , until the spraying is completed; then the sprayed electrode is placed in a vacuum oven to dry at 60°C for 30 minutes.

[0050] 5) Use 760 electrochemical workstation to test the performance of the prepared electrode in electrolysis of ethylene glycol wastewater.

[0051] The X-ray diffraction pattern of the Cu-Ni electrode prepared in this example is as follows: Figure 1 As shown in the SEM images Figure 2 As shown in (a), it can be seen that Cu is evenly distributed on the electrode surface. 2+ Cu 2+ Uniform substitution, the doped trace Cu does not change the crystal structure of the original electrode or introduce a new crystal structure. The catalyst appears as a high-crystallinity β-Ni(OH)2 phase. The oxidation performance curve of the electrode for ethylene glycol is as follows: Figure 3 (a) shows that the current density reaches 100 mA / cm 2 When , the voltage is 1.468V.

[0052] Embodiment 2:

[0053] 1) Catalyst synthesis

[0054] Take 28.5g Ni(NO3)2·6H2O and 0.9375g Cu(NO3)2 and dissolve them in 1L deionized water. Stir magnetically for 10 minutes. The concentrations of nickel salt and copper salt in the aqueous solution are 0.098mol / L and 0.005mol / L, respectively. Add sodium hydroxide to the solution until the pH reaches 13.5. After standing for 30 minutes, pour out the supernatant, then add deionized water and centrifuge. Repeat the centrifugation twice to obtain catalyst powder.

[0055] 2) Prepare catalyst slurry, polymer additive solution and pore-forming agent solution

[0056] Prepare catalyst slurry: take 3g of catalyst, then add 50ml of deionized water and 60ml of ethylene glycol to obtain catalyst slurry, so that the solid content of the catalyst is 2.5wt%, and then disperse the catalyst slurry by vacuum emulsification shearing, high-speed stirring and ultrasound. Set the vacuum emulsification shearing speed to 15000r / min, the time to 60min, the temperature to 20°C, the ultrasonic dispersion time to 20min, and the ultrasonic power to 1200W.

[0057] Prepare polymer additive solution: take 1.2 g of polyamic acid and dilute it to 10 wt % with ethylene glycol.

[0058] Prepare the porogen solution: take 0.5 g of ammonium carbonate and dilute it to 2.5 wt % with isopropanol.

[0059] 3) Nickel foam pretreatment

[0060] Firstly, the commercial nickel foam was immersed in an acetone solution and ultrasonically washed for 20 minutes to remove surface organic matter; secondly, the nickel foam washed with acetone was immersed in a hydrochloric acid aqueous solution and ultrasonically washed for 20 minutes, and the volume ratio of hydrochloric acid to water was 1:3; then, the nickel foam washed with hydrochloric acid was ultrasonically washed with deionized water until the aqueous solution was neutral; finally, the nickel foam rinsed with deionized water was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C for 30 minutes.

[0061] 4) Place the pretreated nickel foam on the spraying base, deliver the prepared catalyst slurry, polymer additive solution and pore-forming agent solution to the spraying chamber through different flow channels, and set the spraying equipment parameters so that the catalyst loading is 2 mg / cm 2 The flow rate of polymer additive solution is 0.8 ml min -1 The flow rate of the pore-forming agent solution is 0.3 ml min -1 , until the spraying is completed; then place the sprayed electrode in a vacuum oven to dry at 60°C for 30 minutes.

[0062] 5) The prepared electrode was tested for its performance in electrolysis of ethylene glycol wastewater using a CHI760E electrochemical workstation.

[0063] The X-ray diffraction pattern of the Cu-Ni(OH)2 electrode prepared in this embodiment is similar to Figure 1 As shown, SEM images are similar to Figure 2 (a) shows the oxidation performance curve of the electrode for ethylene glycol. Figure 3 (b) shows that the current density reaches 100 mA / cm 2, the voltage is 1.451V.

[0064] Embodiment 3:

[0065] 1) Catalyst synthesis

[0066] Take 28.5g Ni(NO3)2·6H2O and 1.875g Cu(NO3)2 and dissolve them in 1L deionized water. Stir magnetically for 10 minutes. The concentrations of nickel salt and copper salt in the aqueous solution are 0.098mol / L and 0.01mol / L, respectively. Add sodium hydroxide to the solution until the pH reaches 13.5. After standing for 30 minutes, pour out the supernatant, then add deionized water and centrifuge. Repeat the centrifugation twice to obtain catalyst powder.

[0067] 2) Prepare catalyst slurry, polymer additive solution and pore-forming agent solution

[0068] Prepare catalyst slurry: take 3g of catalyst, then add 50ml of deionized water and 6.3ml of ethylene glycol to obtain catalyst slurry, so that the solid content of the catalyst is 5wt%, and then disperse the catalyst slurry by vacuum emulsification shearing, high-speed stirring and ultrasound. Set the vacuum emulsification shearing speed to 20000r / min, the time to 10min, the temperature to 35°C, the ultrasonic dispersion time to 60min, and the ultrasonic power to 600W.

[0069] Prepare a polymer additive solution: take 1.2 g of polyamic acid and dilute it to 2.5 wt % with ethylene glycol.

[0070] Prepare the porogen solution: take 0.5 g of ammonium carbonate and dilute it to 10 wt % with isopropanol.

[0071] 3) Nickel foam pretreatment

[0072] Firstly, the commercial nickel foam was immersed in an acetone solution and ultrasonically washed for 18 minutes to remove surface organic matter; secondly, the nickel foam washed with acetone was immersed in a hydrochloric acid aqueous solution and ultrasonically washed for 18 minutes, and the volume ratio of hydrochloric acid to water was 1:3; then, the nickel foam washed with hydrochloric acid was ultrasonically washed with deionized water until the aqueous solution was neutral; finally, the nickel foam rinsed with deionized water was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C for 30 minutes.

[0073] 4) Place the pretreated nickel foam on the spraying base, deliver the prepared catalyst slurry, polymer additive solution and pore-forming agent solution to the spraying chamber through different flow channels, and set the spraying equipment parameters so that the catalyst loading is 2 mg / cm 2 The flow rate of polymer additive solution is 0.8 ml min -1 The flow rate of the pore-forming agent solution is 0.3 ml min -1, until the spraying is completed; then place the sprayed electrode in a vacuum oven to dry at 60°C for 30 minutes.

[0074] 5) The prepared electrode was tested for its performance in electrolysis of ethylene glycol wastewater using a CHI760E electrochemical workstation.

[0075] The X-ray diffraction pattern of the Cu-Ni(OH)2 electrode prepared in this embodiment is similar to Figure 1 As shown, SEM images are similar to Figure 2 (a) shows that the electrode has a similar oxidation performance curve for ethylene glycol. Figure 3 (b) shows that the current density reaches 100 mA / cm 2 , the voltage is 1.457V.

[0076] Comparative Example 1:

[0077] 1) Catalyst synthesis

[0078] Take 28.5g Ni(NO3)2·6H2O and dissolve it in 1L deionized water. Stir it magnetically for 10 minutes. The nickel salt concentration in the aqueous solution is 0.098mol / L. Add sodium hydroxide to the solution until the pH reaches 13.5. After standing for 30 minutes, pour out the supernatant, then add deionized water and centrifuge it. Repeat the centrifugation twice to obtain catalyst powder.

[0079] 2) Prepare catalyst slurry, polymer additive solution and pore-forming agent solution

[0080] Prepare catalyst slurry: take 3g of catalyst, then add 50ml of deionized water and a certain amount of ethylene glycol to obtain catalyst slurry, so that the solid content of the catalyst is 4wt%, and then disperse the catalyst slurry by vacuum emulsification shearing, high-speed stirring and ultrasound. Set the speed of vacuum emulsification shearing to 10000r / min, the time to 30min, the temperature to 25°C, the ultrasonic dispersion time to 30min, and the ultrasonic power to 800W.

[0081] Prepare polymer additive solution: take 1.2 g of polyamic acid and dilute it to 5 wt % with ethylene glycol.

[0082] Prepare the porogen solution: take 0.5 g of ammonium carbonate and dilute it to 3 wt % with isopropanol.

[0083] 3) Nickel foam pretreatment

[0084] First, immerse the commercial nickel foam in an acetone solution and ultrasonically wash it for 15-20 minutes to remove surface organic matter; secondly, immerse the nickel foam washed with acetone in a hydrochloric acid aqueous solution and ultrasonically wash it for 15-20 minutes, with the volume ratio of hydrochloric acid to water being 1:3; then, the nickel foam washed with hydrochloric acid is ultrasonically washed with deionized water until the aqueous solution becomes neutral; finally, the nickel foam rinsed with deionized water is rinsed with anhydrous ethanol and then dried in a vacuum oven at 60°C for 30 minutes.

[0085] 4) Place the pretreated nickel foam on the spraying base, deliver the prepared catalyst slurry, polymer additive solution and pore-forming agent solution to the spraying chamber through different flow channels, and set the spraying equipment parameters so that the catalyst loading is 2 mg / cm 2 The sprayed electrode was placed in a vacuum oven and dried at 60°C for 30 min.

[0086] 5) The prepared electrode was tested for its performance in electrolysis of ethylene glycol wastewater using a CHI760E electrochemical workstation.

[0087] The X-ray diffraction pattern of the Ni electrode prepared in this example is similar to Figure 1 The oxidation performance curve of the electrode for ethylene glycol is shown in Figure 4 (a) shows that the current density reaches 100 mA / cm 2 , the voltage is 1.571V.

[0088] Comparative Example 2:

[0089] 1) Catalyst synthesis

[0090] The Cu-Ni(OH)2 electrode was prepared by electrochemical deposition. 1.425g Ni(NO3)2·6H2O and 0.04675g Cu(NO3)2 were dissolved in 50ml deionized water and magnetically stirred for 10min. The concentrations of nickel salt and copper salt in the aqueous solution were 0.098mol / L and 0.005mol / L, respectively. The constant voltage method was used for electrodeposition. The working electrode and the counter electrode were both pretreated nickel foam electrodes. The reference electrode was Ag / AgCl electrode. The applied voltage was -2V, and the electrodeposition time was 240s. The electrode after electrodeposition was placed in a vacuum oven for drying at 60℃ for 30min. Then, the prepared electrode was tested for the electrolysis of ethylene glycol wastewater using a CHI760E electrochemical workstation.

[0091] The X-ray diffraction pattern of the Ni electrode prepared in this example is similar to Figure 1 As shown in the SEM images Figure 2 As shown in (b), it shows a high degree of particle aggregation, indicating that Cu is unevenly distributed on the electrode surface. The oxidation performance curve of this electrode for ethylene glycol is shown in Figure 4(b) shows that the current density reaches 100 mA / cm 2 When , the voltage is 1.507V.

[0092] The oxidation performance of the catalysts prepared in the examples and comparative examples on ethylene glycol waste liquid is listed in Table 1.

[0093] Table 1 Oxidation performance data of catalysts prepared in Examples and Comparative Examples for ethylene glycol waste liquid

[0094]

[0095] By comparing Examples 1-3 with Comparative Example 1, it can be found that under the same conditions, the electrode prepared by the present invention can significantly improve the electro-oxidation rate of ethylene glycol. Under the same current density, the required potential is lower and the electrode stability is better. It can be found from Examples 1-3 and Comparative Example 2 that, as can be seen from the SEM image, the catalyst on the electrode obtained by ultrasonic spraying is more uniform, the porosity is high, the corresponding active specific surface area is higher, and the electrode stability is better.

[0096] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an electrode for electrolyzing heavy alcohol waste liquid based on nano-ultrasonic spraying technology, characterized in that: The following steps are involved: Step S1: synthesizing catalyst powder; Step S2: preparing catalyst slurry; Step S3: preparing a polymer additive solution; Step S4: preparing a porogen solution; Step S5: dispersing the catalyst slurry by vacuum emulsification shearing, high-speed stirring and ultrasound; Step S6: performing nano-ultrasonic spraying on the electrode for electrolysis of heavy alcohol waste liquid; wherein the electrode is a foamed nickel electrode; Step S7: Turn over the electrode for electrolysis of heavy alcohol waste liquid, and repeat step S6 to spray the other side thereof to obtain the electrode for electrolysis of heavy alcohol waste liquid containing a porous catalytic layer.

2. The method according to claim 1, characterized in that In step S1, the catalyst is copper-doped nickel hydroxide (Cu-Ni(OH)2), and its synthesis process includes the following steps: S101: dissolving nickel salt and copper salt in deionized water to obtain a catalyst salt solution, and controlling the concentrations of nickel salt and copper salt in the obtained solution to be 0.098 mol / L and 0.002-0.01 mol / L, respectively; wherein the nickel salt is Ni(NO3)2·6H2O, and the copper salt is Cu(NO3)2; S102: adding sodium hydroxide to the catalyst salt solution to generate flocculent precipitate, adjusting the pH to 13.5 and then standing for 30 minutes; S103: After the solution has been allowed to stand, the supernatant is discarded, and deionized water is added and centrifuged in a centrifuge for 5 minutes. The operation is repeated twice to obtain catalyst powder.

3. The method according to claim 1, characterized in that In step S2, a first solvent is added to the catalyst, and the mass ratio of the catalyst to the first solvent is controlled to be 1:(20-40); wherein the first solvent is one or more of water, ethylene glycol, isopropanol and propylene glycol.

4. The method according to claim 1, characterized in that In step S3, the polymer is polyamic acid salt, and a second polar solvent is added to the polyamic acid salt, and the mass ratio of the polyamic acid salt to the second polar solvent is 1:(10-40); wherein the second polar solvent is one or more of ethylene glycol, isopropanol and propylene glycol.

5. The method according to claim 1, characterized in that In step S4, the pore-forming agent is ammonium bicarbonate, and a third solvent is added to the pore-forming agent, and the mass ratio of the pore-forming agent to the third solvent is 1:(10-40); wherein the third polar solvent is one or more of ethylene glycol, isopropanol and propylene glycol.

6. The method according to claim 1, characterized in that Step S5 includes the following sub-steps: S501: vacuum emulsification shearing and high-speed stirring: the catalyst slurry obtained in step S2 is subjected to vacuum emulsification shearing, and high-speed stirring is performed simultaneously with vacuum emulsification shearing; S502: Ultrasonic dispersion: Ultrasonic dispersion is performed on the catalyst slurry after vacuum emulsification shearing and high-speed stirring in step S501 to obtain dispersed catalyst slurry.

7. The method according to claim 6, characterized in that In step S501, the rotation speed of the vacuum emulsification shearing is 10000-20000 r / min, the time is 10-60 min, and the temperature is 20-35°C.

8. The method according to claim 6, characterized in that In step S502, the ultrasonic dispersion time is 20-60 minutes, the ultrasonic power is set to 600-1200W, and the ultrasonic frequency is set to 20-40KHz.

9. The method according to claim 1, characterized in that In step S6, the nickel foam electrode requires the following pretreatment steps: S601: Immerse the commercial nickel foam in acetone solution and ultrasonically wash it for 15-20 minutes to remove surface organic matter; S602: immersing the nickel foam obtained in step S601 in a hydrochloric acid aqueous solution for ultrasonic washing for 15-20 minutes; wherein the volume ratio of hydrochloric acid to water in the hydrochloric acid aqueous solution is 1:3; S603: ultrasonically washing the nickel foam obtained in step S602 with deionized water until the aqueous solution becomes neutral; S604: The nickel foam obtained in step S603 is rinsed with anhydrous ethanol and then placed in a vacuum oven for drying at 60° C. for 30 min.

10. The method according to claim 1, characterized in that In step S6, the pretreated nickel foam is placed on the spraying base, and the prepared catalyst slurry, polymer additive solution and pore-forming agent solution are delivered to the spraying chamber through different flow channels. The spraying equipment parameters are set so that the catalyst loading on the electrode is 2 mg / cm 2 The flow rate of polymer additive solution is 0.8 ml min -1 The flow rate of the pore-forming agent solution is 0.3 ml min -1 , until the spraying is completed; then the electrolysis heavy alcohol waste liquid electrode containing a porous catalytic layer obtained by ultrasonic spraying is placed in a vacuum oven for drying at 60°C for 30 minutes to obtain the electrolysis heavy alcohol waste liquid electrode product.

Citation Information

Patent Citations

  • Method for preparing core-shell structure CoP-Ni2P nanorod

    CN109626346A

  • Preparation method of carbon-coated manganese-doped CoP difunctional water decomposition electrode

    CN115786932A

  • Nanometer non-noble metal hydrogen evolution electrode of porous carbon carrier and preparation method of nanometer non-noble metal hydrogen evolution electrode

    CN116377478A